KEKUATAN HUKUM AKTA OTENTIK NOTARIS TANPA DIHADIRI PRNGHADAP (STUDI KASUS PUTUSAN MPWN NOMOR: 03/PTS/MJ.PWN PROVINSI SUMATERA SELATAN/VIII/2014 - Kartika Kartika (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
Notary is an official who owns the authority to produce authentic deed.  Authentic deed is a perfect evidence because it is created in such perfect form based on legal constituation and is made by authorized official who owns goverment trust.  An authentic deed has to obtain several elements as requered by the law.  One main requirement is the presence of “Penghadap”.  “Penghadap” is legit requirement of an agreement and is stated inside the body of an authentic deed.  Therefore presence of a “Penghadap” becomes very vital in determingning authenticity of a deed.  Studi in a case Kekuatan Hukum Akta Otentik Notaris Tanpa dihadiri  Penghadap (Studi Kasus Putusan MPWN Nomor: 03/PTS/MJ.PWN PROVINSI SUMATERA SELATAN/VIII/2014)” showed firstly, that notary TI created copy establishment of LBH Kesehatan stated all the elements were not available and did not signed the deed.Secondly, MPW gave written senction toward notary TI on doing ethical violation,thirdly the deed of establishment is cancelled for law because the “Penghadap” were not presence in the process of deed establishmentKeywords : Notary, Deep, Pengha